A Study on Organizatonal Culture in Sakthi Auto Component Limited, Pallagoundenpalayam - Rekha, S.; Murugan, Muthu (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Organizational culture determines the employees’ perceptions likewise as views of an organization. The research aims to investigate the impact of organizational climate on employee satisfaction in the organization. Organizational culture has been measured on the basis of nine parameters that is: role and responsibility, objectives and goals, leadership and management work environment, performance management, career growth opportunities, work life balance rewards &recognition and pay and benefit. The study determines the relation between components of organizational culture with employee satisfaction. The sample size determined for this study is 245. The Simple random sampling was utilized in this study. The primary data was collected through questionnaire and analyzed with the help of statistical tool namely Percentage analysis, Weighted Average and Chi – square analysis. The findings of the study and recommendation are mentioned. The result obtained highlights the positive relationship between organizational culture.
Keywords: Organizational culture; employee performance; employee satisfaction